Responses to Flooding of Two Riparian Tree Species in the Lowland Tropical Forests of Thailand - Boontida Moungsrimuangdee; Panya Waiboonya; Prapatsorn Yodsa-nga; Panadda Larpkern (Environment and Natural Resources Journal, 2020)
Responses of riparian woody species, especially in the tropical forests of Thailand, under flooding condition remain unknown. The effects of flooding on growth of the native species, Hydnocarpus anthelminthicusand Xanthophyllum lanceatum, which dominate in the lowland tropical forests in the East of Thailand, were observed during 16 weeks. The growth and morphological responses were determinedin one-year-old seedlings, which stems were submerged at a level of 3 cm above the soil surface (flooded). They were compared to the control (unflooded) at every 2, 4, 8, 12, and 16 weeks. Flooding did not suppress shoot elongation in H. anthelminthicusand X. lanceatumover the study period. In general, leaf, stem, and root biomass were not significantly different between flooded and unflooded seedlings in both species. Adventitious roots were found in flooding seedlings of both species, while hypertrophied lenticels were not formed during the submergences. In addition, senescence, necrosis, abscission, or mortality were not observed in the flooded seedlings in this study. Preliminarily, H. anthelminthicusand X. lanceatumcould be considered as potential species for restoring the riparian forest, especially in the studied region.